PRODUCTION OF XYLOSE USING ACID HYDROLYSIS OF WHEAT STRAW - & Shakir, AL-Rubaia’ay (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was conducted to produce xylose by acid hydrolysis from lignocellulose by product . The process of acid hydrolysis carried out using dilute H2SO4 to hydrolyze the available sources of lignocellulosics in Province of Wassit being (corn stover, rice husk, reed and wheat straw) ,wheat straw was selected as the best source for hemicellulose (35)% as compared to the above mentioned sources. The hydrolysis process included two separated experiments ,acid hydrolysis of autoclaved and non- autoclaved wheat straw using the following reaction conditions [(0.5, 1 and 1.5%) sulfuric acid solution, (1, 2 and 3hrs) hydrolysis time and (1:10, 1:15 and 1:20) solid to liquid ratio]. The results indicated that the optimal reaction conditions for the recovery of xylose from autoclaved wheat straw was observed when 1% sulfuric acid solution, 1:15 solid: liquid ratio over 1 hr. incubation time was used . From scaling up to using 10 g wheat straw as substrate, an average xylose yield was 20.61g xylose/100 g of wheat straw (dry basis) . Also, results indicated that the highest level of furfural (0.77) % was observed when 1.5% sulfuric acid solution over 3hrs hydrolysis. while, the lowest level (0.22)% was observed when 0.5% sulfuric acid after 1hr reaction time used, demonstrating that the reaction time and acid concentration has very significant role on concentration of furfural formation.